Case Report: Cognitive Work Hardening for Return-to-Work Following Depression - Wisenthal, Adeena (Frontiers in Psychiatry, 2021)
The growing number of mental health disability claims and related work absences are associated with a magnitude of human, economic and social costs with profound impact on the workplace. In particular, absences due to depression are prevalent and escalating. There is a need for treatment interventions that address the unique challenges of people returning to work following an episode of depression. Occupational functioning often lags depression symptom improvement which necessitates targeted treatment. Cognitive work hardening (CWH) is a multi-element, work-oriented intervention with empirical research supporting its role in return-to-work following a depressive episode. This case report details the use of CWH to prepare an individual to return to work following a disability leave due to depression. It illustrates how CWH bridges the functional gap between being home on disability and returning to competitive employment. The client presented is a 50 year old divorced woman who had been off work for approximately two years for depression precipitated by the terminal illness of her mother. She participated in a four week CWH program which addressed fatigue and decreased stamina, reduced cognitive abilities, outdated computer skills, and heightened anxiety. Work simulations enabled the rebuilding of cognitive abilities with concomitant work stamina; task mastery bolstered self-confidence and feelings of self-efficacy; and coping skill development addressed the need for stress management and assertive communication strategies. By program completion, the client’s self-reported work ability had increased and both fatigue and depression symptom severity had decreased. Clinical markers of work performance indicated that the client was ready to return to her pre-disability job. Three months after completion of CWH, the client reported that she was at work, coping well and working full days with good stamina and concentration. This report provides insight into how CWH can be applied to return-to-work preparation following depression with positive outcomes.